Examination of Universal Racial Differences in Biological Parameters: Analysis Based on Wavelet Interpolation Model - Fujii, Katsunori (European Journal of Applied Sciences, 2022)
It is known that the human body is becoming larger, even when viewed historically. Since around 1900 a remarkable trend has been seen globally. Genetically, this phenomenon has been hypothesized to be a mini-evolutionary phenomenon related to epigenetics, but that has not been clearly verified. However, human growth patterns could be called a universal phenomenon. Even though bodies are becoming larger, there have been no great changes in growth patterns. Eveleth and Tanner [14] showed research trends on global physical growth, and provided valuable findings. The physical growth data shown in that report were published in the 1960s, and so their findings are from analysis of physical growth trends of more than 50 years ago, from an aggregation of research performed with very traditional analytical methods. Therefore, there are no detailed data from analyses of these growth curves with objective methods. While they may be a little old as physical growth data, it would seem foolish to neglect these global scale data without subjecting them to an analysis using scientific methods. By applying the wavelet interpolation model proposed by Fujii [10], we analyzed the global physical growth data shown by Eveleth and Tanner [14], in particular identifying the age at MPV of height as a biological parameter and examining the differences in biological parameters among the human races (Caucasoid, Mongoloid, Negroid, and Australoid).